Peningkatan Kesejahteraan Peternak Sapi Potong Sistem Bagi Hasil di Kecamatan Kulo, Kabupaten Sidenreng Rappang, Propinsi Sulawesi Selatan - A Nugraha; I Syarif; F. R. Saputra (Politeknik Negeri Lampung, 2020)
The purpose of this study was to determine the increase in welfare of beef cattle production sharing systems. Data collection time is from January to February 2020. The research was conducted in Kulo Subdistrict, Sidenreng Rappang District, Survey Research Methodology. A sample of 64 farmers was taken (total sampling). Data analysis method is testing statistical models using SEM SmartPLS (Partial Least Square) 2.0. The results of the study explained that the Improvement of Beef Cattle Farmers' Welfare Sharing in the District of Kulo could be done with strategies to improve the aspects of individual farmers, improve stakeholder relations, and improve the quality of farmers.